Politics of ethnic participation during Khatami's presidency in Iran (1997-2004) - Khorshidi, Majid; Zoeram, Vahid Amani; Lee, Yok Fee; Jawan, Jayum (Canadian Academy of Oriental and Occidental Culture, 2011)
Political participation is considered the most effective instrument for preserving citizens' freedom and rights in modern governments. Moreover, Political participation, as one of the aspects of social participation plays undoubtedly a prominent role in decreasing discrimination against minorities in the contemporary democratic societies. The reformist administration which governed Iran for eight years (1997-2004) and was established on (ex) president Khatami’s ideas and was headed by him, managed some steps toward promoting democracy in Iran. Beside its nation-wide efforts, the administration had its specific ethnic diversity management which encouraged the ethnic groups’ social as well as political participation. Through analysing the data collected by several in-depth interviews with the Iranian elites, this research minds to explore Khatami’s administration policies in the field of promoting ethnic groups participation. Collected data emphasizes on relative success of the administration achieving its aims.